2018
DOI: 10.3892/ol.2018.7988
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits hepatocellular carcinoma growth by targeting VEGF expression

Abstract: Morbidity and mortality owing to hepatocellular carcinoma (HCC), the most common primary liver cancer, has increased in recent years. Curcumin is a polyphenol compound that has been demonstrated to exert effective antiangiogenic, anti-inflammatory, antioxidant, and antitumor effects. However, its clinical effects in HCC remain elusive. The main aim of the present study was to determine the antiangiogenic effects of curcumin in HCC. H22HCC cells were treated with different concentrations of curcumin in vitro. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…Of note, the relationship between curcumin and VEGF has been investigated in several diseases. For example, Pan et al [34] have reported that curcumin reduces cell growth via inhibiting VEGF expression in hepatocellular carcinoma. Lu et al [35] have shown that curcumin can induce human pterygium fibroblast apoptosis via targeting VEGF expression.…”
mentioning
confidence: 99%
“…Of note, the relationship between curcumin and VEGF has been investigated in several diseases. For example, Pan et al [34] have reported that curcumin reduces cell growth via inhibiting VEGF expression in hepatocellular carcinoma. Lu et al [35] have shown that curcumin can induce human pterygium fibroblast apoptosis via targeting VEGF expression.…”
mentioning
confidence: 99%
“…Nature-derived compounds are an important source of drug discovery against various conditions, including HCC. Recently, several natural compounds have been discovered to possess potent anti-HCC activity, including curcumin and its analog, EF25-(GSH)2 [32,33], resveratrol [34], tanshinone IIA [35], and silibinin [36]. Our findings that BBR could inhibit hepatoma cell growth, further strengthening the body of evidence on the anti-HCC bioactivity of this alkaloid [13][14][15], and adds it to the growing list of natural products as lead compounds that warrant further evaluation for the development as anti-HCC therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in traditional Chinese medicine for treating symptoms of hypochondriac pain, mental stress, and mania [25]. 1, 7-bis (4-hydroxy-3-methoxyphenyl)-1, 6-heptadiene-3, 5-dione (curcumin) is the major constituent of curcuma longa, which has found to possess various properties including anti-inflammatory, immunomodulatory, antioxidative, and neuroprotective effects [26].…”
Section: Discussionmentioning
confidence: 99%